(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This study employs big data analytics and SciBERT to conduct cluster and linear regression analyses of research collaboration between China and Malaysia. Originating from China’s "Belt and Road" initiative, this collaboration has evolved into a comprehensive strategic partnership, fostering advancements in economics, agriculture, technology, education, and more. Establishing multi-dimensional strategic relationships aligns with global trends, emphasizing technological innovation’s pivotal role. Both nations have implemented policies to boost science and technology, influencing their collaborative efforts. Research collaboration serves as a driving force for technological progress, intertwining with cultural exchange. The study focuses on the trends, characteristics, and influencing factors of China-Malaysia research collaboration using data from the Web of Science. The findings provide insights for optimizing collaboration models and guiding future policies, contributing to the communication and development between China and Malaysia.